Granular bistable structure with tunable mechanical behaviours - Kwek, Nicholas Yong Kang (Nanyang Technological University, 2023)
Bistability is a phenomenon where a system can exist in two stable states, typically a transition occurs between two states when there is presence of an applied external load. This concept has uses in a variety of disciplines including physics, chemistry, biology, and engineering. Understanding the fundamentals of bistability is crucial in the design of devices such as memory elements and switches. Though bistability has been thoroughly studied in the past, recent developments in experimental techniques and mathematical modelling have offered fresh perspectives on the mechanisms underlying this phenomenon, opening new research directions and potential uses. Therefore, in this study, we will look to use jammable granular material to assemble a bistable structure to explore tunable mechanical behaviour.